Sintesis dan Karakterisasi Hidrogel PVA/Alginat Mengandung Ekstrak Lada sebagai Pembalut Luka Antibakteri - Fadillah Ramadhani; Lizia Miratsi; Zalva Humaeroh; Fitri Afriani (UNIB Press, 2021)
Wound dressings act as wound protectors as well as drug delivery for wound healing. This article develops a PVA/alginate-based wound dressing material added with pepper extract to obtain its antibacterial properties. The sample preparation process consisted of several stages: the preparation of pepper extract by maceration method with ethanol solvent, preparation of PVA/Alginate hydrogel and addition of pepper extract, and testing. Antibacterial test using the paper disc method with the pathogen Staphyloccocus aureus showed that the extract had powerful antibacterial properties with an inhibition zone of about 22 m. Based on the FTIR analysis, it is known that the FTIR transmittance pattern of the PVA/alginate composite added with pepper is related to its constituent functional groups. The highest degree of swelling of the hydrogels prepared in this study was 188%.